Hermite–Hadamard's inequality and Cauchy-type mean operators for positive -semigroups. Issue 1 (1st January 2018) - Aslam, Gul I. Hina; Anwar, Matloob
Abstract: Hermite–Hadamard's-type inequality is derived using superquadratic maps for positive operator semigroups. A methodical procedure was adopted to obtain the corresponding mean operators.